The Belle II Physics Book - Kou, E; Bishara, F; Brod, J; Buras, A J; Ciuchini, M; Deppisch, T; Godfrey, S; Haisch, U; Hirose, S; Kahlhoefer, F; Kamenik, J F; Kronfeld, A S; et al. (Progress of theoretical and experimental physics, 2020)
The Belle II Theory Interface Platform (B2TiP) was created as a physics prospects working group of the Belle II collaboration in June 2014. It offered a platform where theorists and experimentalists could work together to elucidate the potential impacts of the Belle II program, which includes a wide scope of physics topics: B physics, charm, τ, quarkonium physics, electroweak precision measurements, and dark sector searches.